From fear to resilience: adolescents' experiences of violence in inner-city Johannesburg, South Africa - Fiona Scorgie; Deborah Baron; Jonathan Stadler; Emilie Venables; Heena Brahmbhatt; Kristin Mmari; Sinead Delany-Moretlwe (BMC, 2017)
Abstract Background For adolescents growing up in poor urban South African settings, violence is often a part of daily life and has lasting effects on physical and mental health outcomes in adulthood. We conducted a qualitative study to document and understand the forms of interpersonal violence experienced by adolescents living in Hillbrow, Johannesburg. In this article, we explore how violence is experienced differently by adolescent boys and girls, how they conceptualise 'dangerous' and 'safe' spaces in their neighbourhood and what gaps exist in available services for youth in Hillbrow. Methods The article draws on data collected in the formative phase of the 'Wellbeing of Adolescents in Vulnerable Environments' (WAVE) Study of challenges faced by adolescents (15-19 years) growing up in impoverished parts of five cities. This article reports on analysis using only data from the Johannesburg site. Using both purposive and snowball sampling to select participants, we conducted in-depth interviews (n = 20) and community mapping exercises with female (n = 19) and male (n = 20) adolescents living in Hillbrow, as well as key informant interviews with representatives of residential shelters, CBOs, and NGOs working with youth (n = 17). Transcripts were coded manually and analysed using an inductive thematic analysis approach. Results Both girls and boys reported high exposure to witnessing violence and crime. For girls, the threat of sexual harassment and violence was pervasive, while boys feared local gangs, the threat of physical violence, and being drawn into substance-abuse. Home was largely a safe haven for boys, whereas for girls it was often a space of sexual violence, abuse and neglect. Some adolescents developed coping mechanisms, such as actively seeking out community theatres, churches and other places of sanctuary from violence. Community-based services and shelters that support adolescents reported a lack of resources, overall instability and difficulties networking effectively. Conclusions Adolescents in Hillbrow commonly witnessed and had direct experience of many forms of violence in their environment, and these experiences differed markedly by gender. Interventions that build young peoples' social capital and resilience are essential for reducing violence-related trauma and long-term health and social consequences for adolescents in this community.